An Inquiry on Desensitization to Violence and its Relation with Social Media - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2017)
The study examines the presence of violence and its dimensions in the social realm through the exploration of social networking site Facebook. It focuses on understanding users' attitude towards violent content. As the study tests that once the violent content posted or shared with a purpose of being sensitive it actually leavens the roots of desensitization; it is thus thought that it could contribute and shed light on the future studies related with social media effect on individual perception and social values in the long term. With this purpose, the methods of questionnaire and qualitative content analysis were used to observe the implications of violent content in the frame of desensitization. It is concluded that once the violent content is mediated by the social media it becomes decontextualized and meaningless.
Keywords: Facebook; Violence; Desensitization; Social Media; VIDEO GAMES; AGGRESSION; ADOLESCENTS; BEHAVIOR; TELEVISION; ATTITUDES; EXPOSURE; CHILDREN; OTHERS; LIFE